MANAJEMEN PENGELOLAAN KEUANGAN KELUARGA DALAM PERSPEKTIF BUDAYA SUMBA: (Studi Kasus Adat Istiadat Perkawinan Di Desa Wee Rame Kabupaten Sumba Barat Daya) - Aprita Susanti Manu; Ida Bagus Raka Suardana (Berajah Journal, 2026)
This study aims to analyze family financial management from a Sumbanese cultural perspective, specifically as it relates to the traditional belis wedding tradition in Wee Rame Village, Southwest Sumba Regency. The belis phenomenon, which involves the economic exchange of livestock, woven fabric, jewelry, and cash, requires families to prepare a well-structured financial situation. This research used a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation involving couples involved in traditional weddings, their families, and traditional leaders. The study focused on aspects of planning, organizing, implementing, and controlling family financial management. The results are expected to provide an understanding of the relationship between financial literacy and local cultural practices, while also uncovering the challenges and conflicts that often arise from differences in fulfilling belis obligations. Theoretically, this research enriches the literature on financial management based on local wisdom. Practically, this research can serve as a reference for the community, government, and social institutions in formulating economic empowerment strategies rooted in culture. Thus, this research contributes to the preservation of Sumbawa culture while improving family economic well-being.